2012
DOI: 10.1016/j.immuni.2012.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Transport Antigen from the Dermis to the Bone Marrow, Initiating a Source of Memory CD8+ T Cells

Abstract: The bone marrow (BM) has been identified as a possible organ for T cell priming, yet the fundamental mechanisms of a polyclonal immune response in the BM remain unknown. We found that after intradermal injection of modified vaccinia Ankara virus, unexpected sources of newly primed polyclonal virus-specific CD8(+), but not CD4(+), T cells were localized in the BM and the draining lymph nodes (dLNs) prior to blood circulation. We identified neutrophils as the virus-carrier cells from the dermis to the BM. In bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
112
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(116 citation statements)
references
References 42 publications
3
112
0
1
Order By: Relevance
“…For IL-8, an indicator for severity of inflammation and attractant of neutrophils, our qRT-PCR results indicate a barrier reconstitution after 24 h, which is coherent with our findings in skin physiology measurements for ex vivo probes [32,33]. IL-8 is a chemoattractant for neutrophils that also play a role in linking neutrophils to the adaptive immunity [34]. An increase is normally seen shortly after barrier perturbation as a sign of inflammation [15,16,35].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…For IL-8, an indicator for severity of inflammation and attractant of neutrophils, our qRT-PCR results indicate a barrier reconstitution after 24 h, which is coherent with our findings in skin physiology measurements for ex vivo probes [32,33]. IL-8 is a chemoattractant for neutrophils that also play a role in linking neutrophils to the adaptive immunity [34]. An increase is normally seen shortly after barrier perturbation as a sign of inflammation [15,16,35].…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, our early trials using CSSS for transcutaneous immunization also pointed towards systemic cytokine increase after influenza transcutaneous vaccination, e.g., IL-8 was elevated in transcutaneous vaccinated individuals [19]. An increase in expression of GM-CSF, a pro-inflammatory cytokine that enhances neutrophil and monocyte function, was observed indicating a role in early immune response [23,24,34,35]. The ex vivo qRT-PCR measurements showed a change in gene expression for IP-10 and TGF-β, both modulators that contribute to the induction of Langerhans cells and dendritic cell maturation as well as the positioning of CXCR3-positive T cells in the skin [16,23,24,36].…”
Section: Discussionmentioning
confidence: 99%
“…This is not entirely unexpected, as CCR1 appears to be expressed on distinct subsets of T lymphocytes and is important for T cell migration to the lymph nodes (62). In addition CCR1 was also shown to play a role in an antigen transport mechanism whereby antigenloaded neutrophils migrate to the bone marrow, where a distinct subset of CD8 ϩ T cells is induced (10). In summary, we have demonstrated that CCR1 is important for MVA-triggered leukocyte migration in vivo, particularly with regard to neutrophil and inflammatory monocyte recruitment.…”
Section: Discussionmentioning
confidence: 86%
“…Systemic myxoma virus infection induces neutrophil recruitment to the liver microvasculature, where adherent neutrophils form large aggregates with platelets, releasing neutrophil extracellular traps that help to prevent infection of adjacent cells (9). Recent studies have indicated that the role of neutrophils during poxvirus infection may extend beyond direct antiviral activity, as during infection with modified vaccinia virus Ankara (MVA), neutrophils transport antigen from the dermis to the bone marrow, where a distinct subset of virus-specific CD8 ϩ T cells is induced (10). This reverse transmigration of neutrophils was mediated by chemokine (C-C motif) receptor 1 (CCR1), a chemokine receptor that seemingly fulfills a number of nonredundant functions in host defense (11).…”
mentioning
confidence: 99%
“…Distinct poxvirus vectors induce substantial differences in chemokine and cytokine profiles (21), which influence the adaptive immune responses. Whereas DCs and neutrophils transport VACV antigens to lymphoid organs and directly induce antigen-specific T cell responses (22,23), NK cells can generate the environment necessary to induce recruitment of activated T cells (20) or cross talk with DCs for the generation of antigen-specific T cell immunity (24).…”
mentioning
confidence: 99%